Down-regulation of connexin 43 contributes to structure and function of pulmonary artery in nicotine-administered mice. (15th March 2023) - Qin, Xiaojiang; Hou, Xiaomin; Xu, Xinrong; Chen, Liangjin; Gao, Anqi; Hao, Yuxuan; Du, Xufeng; Zhao, Liangyuan; Shi, Yiwei; Li, Qingshan
Abstract: Dysregulated connexin signaling is implicated in the pathophysiology of pulmonary artery hypertension (PAH). Nicotine affects pulmonary vascular remodeling. However, the potential mechanistic link between connexin signaling and nicotine-induced pulmonary artery remodeling remains unclear. We aimed to investigate the role of connexin 43 (Cx43) in pulmonary artery remodeling in nicotine-administered C57BL/6 J wild-type (WT) and Cx43 heterozygous (Cx43 +/− ) mice. Hemodynamic parameters and right ventricle pathology were assessed in the mice. Serum biochemical indices of hepatic and renal function were measured. The RT-PCR, immunofluorescence, and western blotting were conducted to evaluate Cx43 mRNA and protein levels. We performed histological staining to identify pulmonary arteries. Wire myography was used to examine contraction and relaxation responses in the pulmonary arteries. Pulmonary vascular permeability was assessed through Evans blue staining. Compared with the WT group, the Cx43 +/- group showed lower Cx43 mRNA and protein expression in the pulmonary arteries ( P  < 0.01). Nicotine treatment significantly increased Cx43 expression ( P  < 0.01) and induced morphological changes in the pulmonary arteries ( P  < 0.01). Our findings suggest that Cx43 plays a crucial role in pulmonary artery reactivity and permeability in mice. Furthermore, downregulation of Cx43 expression may contribute to alterations in pulmonary artery structure and function. Highlights: Nicotine adversely affects blood lipids and liver and kidney function in mice. Connexin43 (Cx43) plays a key role in pulmonary artery remodeling. Cx43 modulates pulmonary artery reactivity and permeability in WT and Cx43 +/- mice. Cx43 affects pulmonary artery structure and function in nicotine-administered mice.